2017
DOI: 10.7771/2159-6670.1162
|View full text |Cite
|
Sign up to set email alerts
|

Safety Climate of Ab-Initio Flying Training Organizations: The Case of an Australian Tertiary (Collegiate) Aviation Program

Abstract: A healthy safety culture is essential to the safe operation of any aviation organization, including flight schools. This study aimed to assess the safety climate of an Australian tertiary (collegiate) aviation program using a self-constructed instrument. Factor analysis of the instrument identified four safety themes, which are Safety Reporting Culture, Safety Reporting Procedure, Organizational Culture and Practice, and General Safety Knowledge. The responses of student pilots suggested that the overall safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Collegiate aviation programs, contrary to commercial aviation, are not governed as strictly in regard to fatigue management systems (Ashley, 2013;Gao & Rajendran, 2017;Government Accountability Office, 2018). A flight instructor's legal work limit of eight hours is frequently one of the few existing policies (Aviation Supplies and Academics, Inc., 2018).…”
Section: Fatigue Mitigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Collegiate aviation programs, contrary to commercial aviation, are not governed as strictly in regard to fatigue management systems (Ashley, 2013;Gao & Rajendran, 2017;Government Accountability Office, 2018). A flight instructor's legal work limit of eight hours is frequently one of the few existing policies (Aviation Supplies and Academics, Inc., 2018).…”
Section: Fatigue Mitigationmentioning
confidence: 99%
“…It could be effective in assessing and mitigating risks because many aeromedical risks are combined in a memorable acronym that can be used with effective results during pre-flight briefings (Gelfand, 2013;Wright, 2017). Student pilots reported to both understand and apply this checklist in their flight training (Gao & Rajendran, 2017). However, the tool only warns of risks but does not offer mitigating strategies, rendering it lesseffective as a real-time assessment tool (Wright, 2010).…”
Section: Fatigue Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been extensive research performed on safety culture and safety climate in industries outside aviation (Barbaranelli et al, 2015;Brondino et al, 2012;Fugas et al, 2012;Groves et al, 2011;Kapp, 2012;Neal et al, 2000;Stemn et al, 2019;Wu et al, 2010). An area of research that is developing is safety culture in collegiate aviation and similar flight training organizations (Adjekum, 2014(Adjekum, , 2017Adjekum et al, 2016;Chiu et al, 2019;Dillman et al, 2010;Gao & Rajendran, 2017;Robertson, 2016). A behavioral component of safety culture that is relevant to this study is safety reporting behavior.…”
Section: Safety Culture In Collegiate Aviationmentioning
confidence: 99%
“…In a study on safety reporting among collegiate aviation programs with SMS, Robertson (2016) suggested that trust in a confidential safety reporting system is a sign of positive safety culture, and Jausan et al (2017) suggested that assessing safety reporting behavior can be beneficial in improving the performance of SMS. Gao and Rajendran (2017) assessed students from an Australian collegiate aviation program using a self-constructed instrument from an earlier study (Gao et al, 2013) and identified four themes: safety reporting culture, safety reporting procedures, organizational culture practice, and general safety knowledge relevant to the topic of safety reporting behaviors. A more in-depth analysis suggested that first-year students had a more positive perception than the students who have been in the program for longer.…”
Section: Safety Culture In Collegiate Aviationmentioning
confidence: 99%